Creatine supplementation in Walker-256 tumor-bearing rats prevents skeletal muscle atrophy by attenuating systemic inflammation and protein degradation signaling - Cella, Paola S.; Marinello, Poliana C.; Borges, Fernando H.; Ribeiro, Diogo F.; Chimin, Patrícia; Testa, Mayra T. J.; Guirro, Philippe B.; Duarte, José A.; Cecchini, Rubens; Guarnier, Flávia A.; Deminice, Rafael (European journal of nutrition, 2020)
Purpose The aim of this study was to investigate the effects of creatine supplementation on muscle wasting in Walker-256 tumor-bearing rats. Methods Wistar rats were randomly assigned into three groups ( n = 10/group): control (C), tumor bearing (T), and tumor bearing supplemented with creatine (TCr). Creatine was provided in drinking water for a total of 21 days. After 11 days of supplementation, tumor cells were implanted subcutaneously into T and TCr groups. The animals’ weight, food and water intake were evaluated along the experimental protocol. After 10 days of tumor implantation (21 total), animals were euthanized for inflammatory state and skeletal muscle cross-sectional area measurements. Skeletal muscle components of ubiquitin–proteasome pathways were also evaluated using real-time PCR and immunoblotting. Results The results showed that creatine supplementation protected tumor-bearing rats against body weight loss and skeletal muscle atrophy. Creatine intake promoted lower levels of plasma TNF-α and IL-6 and smaller spleen morphology changes such as reduced size of white pulp and lymphoid follicle compared to tumor-bearing rats. In addition, creatine prevented increased levels of skeletal muscle Atrogin-1 and MuRF-1, key regulators of muscle atrophy. Conclusion Creatine supplementation prevents skeletal muscle atrophy by attenuating tumor-induced pro-inflammatory environment, a condition that minimizes Atrogin-1 and MuRF-1-dependent proteolysis.